Prevalencia y factores etiológicos de hipoplasia del esmalte incisivo-molar en niños de 7-12 años que asisten a la unidad educativa Pompilio Reinoso Jaramillo periodo noviembre 2018- marzo 2019 - Torres Suquilanda, Cinthya Paulina (2020)
Incisor-molar hypoplasia (HIM) is a quantitative defect in enamel formation. It refers to a decrease in the amount of enamel formed and not the quality of the calcification. This research aimed to know the prevalence and etiological factors of Hypoplasia of the incisor-molar enamel in children aged 7-12 years who attend the Educational Unit "Pompilio Reinoso Jaramillo", period November 2018- March 2019. The type of study was descriptive-cross-sectional, with the application of a survey to know the prevalence and identify the possible etiological factors that may influence the appearance of this pathology. The sample consisted of 120 children from 7 to 12 years old, presenting 26 children (E) Hypoplasia of the Enamel equivalent to 21.67% of the total study population. A higher prevalence was found in children between the ages of 8 and 9 years, as well as the most affected gender was males with a percentage of 73.1%. A relationship was observed with: the consumption of antibiotics, patients who presented low birth weight, and a statistically significant relationship with academic instruction (Secondary) and the number of children of the representatives. The prevalence of the pieces most affected by enamel hypoplasia were the molars, presenting a percentage of 11.2% in the teeth 16, 26, 46. Regarding severity, the Wetzel and Reckel table of values was taken as a reference, the results indicate a higher incidence of grade 1 enamel hypoplasia (less than 1/3) in extension, with a percentage of 46.60%; and a 71.20% prevalence of grade 1 (cream-white) in appearance. Keywords: children, hypoplasia, tooth enamel, amelogenesis